(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2022)
Based on the great importance of the groundbreaking work "The Constitution for them: constitutional interpretation from the perspective of women", which is concerned with offering the interpretation of the Constitution by "them", it is considered essential to look at the political participation of women in Brazilian society. People’s interference in political decision-making in society is not merely symbolic in the sense that it is recognized; on the contrary, it gives those who take part a feeling of "social belonging", no longer being invisible within the society in which they participate. Pondering historical evolution, it can be seen that formal equality was first achieved in many countries and also in Brazil. However, in a state that is characterized as democratic, based on the pillars of freedom and equality, there are still some challenges to be faced in terms of so-called material equality. Although in the majority of democratic countries in the West women formally won their political rights by the middle of the 20th century, as was the case in Brazil itself, it is not possible to say that this was automatically reflected in the achievement of substantive gender equality. In order to identify these challenges in recognizing gender equality and, in particular, women’s participation in political decision-making, this article first looks at the historical issue linked to popular participation, the exercise of citizenship and its reflections in the light of gender equality. Next, we look at the current perception of gender equality in politics and what still stands in the way of equal democracy. Finally, based on the need for a cultural change in the conception that privileges men over women, the constitutional premises and guidelines for the effectiveness of gender equality in Brazilian society are analyzed.